Industry Mix, Local Labor Markets, and the Incidence of Trade Shocks - Yi, Moises; Mueller, Steffen; Stegmaier, Jens (Journal of Labor Economics, 2024)
We analyze how skill transferability and the local industry mix affect the adjustment costs of workers hit by a trade shock. Using German administrative data and novel measures of economic distance, we construct an index of labor market absorptiveness that captures the degree to which workers from a particular industry are able to reallocate into other jobs. Among manufacturing workers, we find that the earnings loss associated with increased import exposure is much higher for those who live in the least absorptive regions. We conclude that the local industry composition plays an important role in the adjustment processes of workers.